The knee extensor moment arm is associated with performance in male sprinters - Miyake, Y.; Suga, T.; Otsuka, M.; Tanaka, T.; Misaki, J.; Kudo, S.; Nagano, A.; Isaka, T. (European Journal of Applied Physiology, 2017)
Purpose: Although large knee extensor torque contributes to superior sprint performance, previous findings have indicated that the quadriceps cross-sectional area (CSA), a pivotal morphological regulator of knee extensor torque, is not correlated with performance in sprinters. We hypothesized that the knee extensor moment arm (MA), another main morphological regulator of knee extensor torque, may affect sprint performance. To test this hypothesis, we examined the relationship between knee extensor MA and sprint performance. Methods: The quadriceps CSA and knee extensor MA in 32 well-trained male sprinters and 32 male non-sprinters were measured using magnetic resonance imaging. Results: Knee extensor MA, but not quadriceps CSA, was greater in sprinters than in non-sprinters (P = 0.013). Moreover, knee extensor MA, but not the quadriceps CSA, was correlated with the personal best time in a 100-m race in sprinters (r = -0.614, P < 0.001). Furthermore, among 24 sprinters who participated in the 60-m sprint test, knee extensor MA was correlated with sprinting velocities in the acceleration (r = 0.717, P < 0.001) and maximum speed (r = 0.697, P < 0.001) phases. Conclusion: The present study demonstrates that the knee extensor MA is greater in sprinters than in non-sprinters, and this morphological structure in sprinters is associated with sprint performance. Therefore, for the first time, we provided evidence that a greater knee extensor MA in sprinters may be an advantageous for achieving superior sprint performance.